Can Japanese aid be an effective tool of influence? case studies of Cambodia and Myanmar - Mikio Oishi; Fumitaka Furuoka (University California Press, 2003)
This article investigates the emerging pattern of Japan’s peacemaking in Southeast Asia, which is characterized by the heavy use of economic aid. Case studies of Cambodia and Burma suggest that Japan’s strength lies in mediation between conflicting parties, not in promoting certain values such as human rights.